Residents’ Health Awareness of the Sustainability of Indoor Air Quality in High Rise Building - Nurwidyaningrum, Dyah; S. Moersidik, Setyo; Suganda, Emirhadi; Kusnoputranto, Suganda (International Journal of Engineering and Technology, 2018)
This study was concerned with the residentsâ€™ health awareness of their behavior which affected indoor air quality (IAQ) in high rise building in Jakarta, Indonesia.Â This analysis was aimed to describe the difference between the strength of the influence of residentsâ€™ dimension to IAQ in unit with knowledge variable and that of without knowledge variable. The behavior based on health knowledge became the parameter of health awareness. The descriptive result indicated that the residents in Rusunami high rise building were well-educated people but not all of them had good behavior.Â Participants whose occupations are related to health tended to take care of indoor air quality better than those from other occupation. With the structural equation modeling (SEM), the construct of residentsâ€™ dimension was formulated based on physical and psychological comfort,Â as well as involvingÂ the healthy life participation and pollution activities. It was found that this combination drove behavioral change to IAQ in high rise building.Â Partial Least Square analysis showed that the knowledge of IAQ could raise the effect of residentsâ€™ dimension to IAQ in unit from 15.2% to 16.6%.Â Â